The preparation of epigraphs in the Middle Ages: The minutes. (Edad Media. Revista de Historia, 2020)
The process of making the medieval inscriptions is one of the least labored aspects in Medieval Epigraphy so far. To a large extent, this is due to the lack of preserved evidence related to how this process could have been done. Pioneering works by professors García Lobo and Martín López suggest that this process should not have been very different to the one used in the studios of the classical period which is well documented. Until now, we have moved on the theoretical level waiting for evidences that could indicate how this process truly was.However, we have preserved information about the existence of small annotations -minutes- where it was collected the data that would later be translated to the epigraphic mounting. Sometimes the full text was included and sometimes only brief annotations with the most significant data that later would be completed with traditional forms. It is considered to be the first phase of the epigraphic conscriptio. However, in current studies we have also verified the existence of these drafts in stone whose meaning and importance we want to highlight in the lines that follow.
Keywords: Medieval Epigraphy; Genesis; Minutes; Epigraphic Production; Medieval Studios; Artist; Romanesque